2015
DOI: 10.5539/ijef.v7n2p178
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Foreign Direct Investment on Economic Growth: Empirical Evidence from Bangladesh

Abstract: Abstract:The study is conducted to find out the impact of foreign direct investment (FDI) on economic growth of Pakistan. Time series data is utilized which is comprises from 1981 to 2010, collected from the world data bank. Multiple regression technique is used in which gdp is dependent variable while foreign direct investment (FDI) and consumer price index (CPI) are independent variables. The result indicates that there is a positive relationship between the FDI and GDP and have a negative relationship with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
50
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 25 publications
9
50
0
1
Order By: Relevance
“…FDI is found to be negatively linked with the growth of the economy which is also an empirically tested fact in the literature as reported by (Quazi, 2004;Eller, Haiss, & Steiner, 2005;K. Rahman, 2008;A. Rahman, 2015).…”
Section: Regression Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…FDI is found to be negatively linked with the growth of the economy which is also an empirically tested fact in the literature as reported by (Quazi, 2004;Eller, Haiss, & Steiner, 2005;K. Rahman, 2008;A. Rahman, 2015).…”
Section: Regression Resultsmentioning
confidence: 60%
“…It may also cause crowding out of domestic capital and a rise in the imports of the host country, as, Foreign Investment' companies usually need high technology machinery and intermediate goods that may not be available in the host country (A. Rahman, 2015;Quazi, 2004;Eller et al, 2005;K. Rahman, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the net inflow of FDI may be negative if the amount of outflow is higher than the amount of new investment. A large number of factors are responsible for hampering positive outcomes from foreign direct investment in Bangladesh, like inadequate infrastructure, a slow-moving privatization process, an unskilled labor force, inefficient bureaucracy, political instability, and recurring natural disasters [32]. This finding can be related to the research of Azam [7], where the researcher found the negative and significant impact of FDI on economic growth.…”
Section: Resultsmentioning
confidence: 93%
“…Tabssum and Ahamed (2014) examined the effects of domestic investment and FDI on economic growth, and reported that domestic investment is more significant than FDI for economic growth of the country. Rahman (2015) showed that FDI and growth has negative correlation. The mixed findings of the causal relationship between FDI and growth encouraged us to further investigate the short-and long-run nature of relationships between the variables.…”
Section: Nexus Of Fdi and Economic Growthmentioning
confidence: 99%
“…Thirdly, studies on the effects of political instabilities on economic performances have ignored the moderating role of political instability on the relationship between economic growth and stock market development, relationship between economic growth and FDI, and relationship between FDI and stock market development (inter alia: Ahmed & Pulok, 2013;Aisen & Veiga, 2013;Alesina & Perotti, 1996;An et al, 2016;Asteriou & Siriopoulos, 2000;Brada et al, 2006;Liu et al, 2017;William, 2017). Similarly, the existing empirical studies mainly focused on the endogenous relationship among economic growth, FDI, and stock market development, whereas, the moderating effect of political instability on these relationships has been given less attention (inter alia: Ang & McKibbin, 2007;Bengoa & Sanchez- Robles, 2003; Brambila-Macias & Massa, 2011;Bristy, 2014;Calderona & Lin, 2003;Chakraborty & Basu, 2002;Handa & Khan, 2008;Haque & Fatima, 2011;Hassan, Sanchez, & Yu, 2011;Hsiao &Hsiao, 2006;Iamsiraroj, 2016;Jalil et al, 2010;Li & Liu, 2005;Masuduzzaman, 2014;Nain & Kamaiah, 2014;Pan & Mishra, 2016;Rahman, 2015;Raza & Jawaid, 2014;Raza, Jawaid, Afshan, & Abd-Karim, 2015;Sahu & Dhiman, 2011;Sehrawat & Giri, 2015;Soumare & Tchana, 2015;Uddin, Shahbaz, Arouri, & Teulon, 2014;Uddin et al, 2014;Freckleton, Wright, & Craigwell, 2012;Yildirm, Ozdemir, & Dogan, 2013;You...…”
Section: Introductionmentioning
confidence: 99%